Pengaruh Periklanan, Promosi Penjualan dan Pemasaran Langsung Terhadap Keputusan Kunjungan Wisatawan - Heri Setiawan; Jusmawi Bustan (Jurnal Riset Bisnis dan Investasi, 2017)
The development of tourism in Indonesia continues to grow rapidly and become one of the sectors that play a major role in developing the economy and improving people's welfare. This study aimed to determine the effect of advertising, sales promotion and direct marketing on decision tourist visits (study on Water Fun Palembang). Respondents selected is the visitor of Water Fun amounted to 120 people. The sampling technique used in this research is purposive sampling, the researchers used their own judgment by way of deliberate in selecting members of the population which are considered to provide specific information in accordance with the desired criteria researchers. The effect of advertising variable on the decision of tourist to visit is 0.391. The effect of sales promotion variables on the decision of tourist to visit is 0.240. There is an effect of direct marketing variables on the decision of the tourist to visit amounted to 0.334. Manager of Water Fun Palembang should maintain and where possible to improve the promotion through advertising, sales promotion and direct marketing so that tourists will still decide to visit Water Fun.